The Great Kosher Meat War of 1902 : Immigrant Housewives and the Riots That Shook New York City - Seligman, Scott D. (Book collections on Project MUSE., 2020)
"The Great Kosher Meat War of 1902 recounts the inspiring story of immigrant women and the dramatic and effective mass consumer action they launched in turn of the century New York City"--